Acne Infection (Acne Vulgaris) and the Relationship between Cutibacterium Acnes Colonization and Severity - Nurafidah Kasmal; Andy Visi Kartika; Nurul Rumila Roem (PSPP JOURNALS, 2026)
Acne vulgaris is a chronic inflammatory disorder of the pilosebaceous unit that commonly affects adolescents and young adults and can significantly impair quality of life. Recent evidence indicates that acne severity is influenced not only by the presence of Cutibacterium acnes but also by the characteristics of specific bacterial strains, their virulence factors, and interactions within the skin microbiome. This study aimed to analyze the relationship between C. acnes colonization and the severity of acne vulgaris through a narrative literature review. Secondary data were obtained from scientific publications indexed in databases such as PubMed, Google Scholar, DOAJ, and other open-access journal portals. The literature search used keywords including “Cutibacterium acnes,” “acne vulgaris,” “biofilm,” “microbiome,” “strain virulence,” and “antibiotic resistance.” Articles published between 2020 and 2025 in Indonesian or English were included. Ten studies met the inclusion criteria and were analyzed using narrative synthesis. The findings indicate that pathogenic phylotypes, particularly IA1 and IC, are more frequently associated with moderate to severe inflammatory acne lesions. These strains demonstrate higher virulence through increased lipase and porphyrin production, strong biofilm formation, and activation of inflammatory pathways such as TLR2-mediated cytokine release. Additionally, microbiome dysbiosis and rising antibiotic resistance to clindamycin and macrolides contribute to persistent inflammation and treatment challenges. Overall, acne severity is influenced more by strain characteristics and microbial interactions than by bacterial quantity alone, highlighting the importance of strain-level analysis and precision-based therapeutic strategies in acne management.